Microsoft project server 2013 : managing projects and portfolios - Chefetz, Gary L. (Chefetz LLC dba MSProjectExperts New YorkUS, 2013)
Presents information on the Microsoft Project Server 2013 solution which covers and applies to both Project Online, the name for Project Server in Microsoft's Office 365 environment, and on-premises Project Server in which Microsoft has introduced a bundle of new project and work management oriented funtionality into SharePoint 2013.